2015
DOI: 10.1109/tse.2015.2421279
|View full text |Cite
|
Sign up to set email alerts
|

Practical Combinatorial Interaction Testing: Empirical Findings on Efficiency and Early Fault Detection

Abstract: Combinatorial Interaction Testing (CIT) is important because it tests the interactions between the many features and parameters that make up the configuration space of software systems. Simulated Annealing (SA) and Greedy Algorithms have been widely used to find CIT test suites. From the literature, there is a widely-held belief that SA is slower, but produces more effective tests suites than Greedy and that SA cannot scale to higher strength coverage. We evaluated both algorithms on 7 real-world subjects for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…There exist several tools and techniques for CIT. Good surveys of ongoing research in CIT can be found in [9,19], while an introduction to CIT and its efficacy in practice can be found in [15,21].…”
Section: Combinatorial Models Of Configurable Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…There exist several tools and techniques for CIT. Good surveys of ongoing research in CIT can be found in [9,19], while an introduction to CIT and its efficacy in practice can be found in [15,21].…”
Section: Combinatorial Models Of Configurable Systemsmentioning
confidence: 99%
“…It is a very popular black-box testing technique that tests all interactions between any set of t parameters. There have been several studies showing the successful efficacy and efficiency of the approach [13,14,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the efficiency of combinatorial t-way testing, Petke et al [15] investigate fault detection effectiveness of combinatorial t-way test suites (2 ≤ t ≤ 6) that are generated by a simulated annealing algorithm, CASA [19], and a greedy algorithm, ACTS [18]. They also examine the fault detection rate of test prioritization of the t-way test suites w. r. t. t -way interaction coverage with 2 ≤ t ≤ 6, which means the test suites whose test cases are re-ordered in the descent order of t -way coverage.…”
Section: Related Workmentioning
confidence: 99%
“…While we in this paper explore weight coverage and KL divergence with fault detection effectiveness of prioritized combinatorial testing with weighted SUT, the work [15], [7], [8] consider combinatorial testing with non-weighted SUT and investigate neither weight coverage nor KL divergence.…”
Section: Related Workmentioning
confidence: 99%